BAGAIMANA MENUMBUHKAN MORAL ETIKA PANCASILA YANG TUMBUH DI NEGARA PANCASILA (SILA KEMANUSIAAN YANG ADIL DAN BERADAB) - Sumantri (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
The point of returning to the important part of Pancasila 5 is that the numbers are not Pancadarma (Darma = obligation) Sila means the principle or basis as the basis for the nation, accommodating differences in diversity, as an open ideology. The values of Pancasila are a form of noble character of Indonesian people which distinguishes them from humans from other countries. Sila means Principles When someone speaks, behaves and behaves according to the values of Pancasila, it shows the nobility of dignity as a civilized nation, the importance of building a national mentality with Pancasila morals and morals that are believed to be true as the source of all sources of law and a way of life Indonesian nation without exception. Pancasila as a filter for the Indonesian nation is used as a life guide for all government administration related to the morality and mentality of the bureaucratic apparatus. Pancasila as an indicator and parameter of the nation's personality. If there is fraud in state life, it is categorized as incompatible with the values of Pancasila.